A Rare Case of Sino-Nasal Teratocarcinosarcoma (Response to Induction Chemotherapy) - Rauf, Muhammad Haris; Asma Asghar; Ali Zafar Sheikh; Anis-ur-Rehman; Kashif Siddique (Pakistan Armed Forces Medical Journal, 2024)
We are presenting a rare case of sino-nasal teratocarcinosarcoma. A 43-year-old male patient presented with repeated episodes of epistaxis and headache for 3 months. On examination, the ENT consultant noticed a mass in the right nasal cavity for which biopsy was performed and CT scan advised. Sinonasal teratocarcinosarcoma was diagnosed on biopsy and immunohistochemistry. CT Face followed by PET/CT showed a FDG-avid soft tissue density mass in the right nasal cavity extending locally with a standardised uptake value of 7.4 with no distant metastasis. Surgical debulking is the first line of treatment as per the literature; however, in this case, the multidisciplinary tumour board initiated induction chemotherapy of 02 cycles of CISP/DOC owing to marked local extension of the tumour. Subsequent CT scan of the face shows a good treatment response with shrinkage of the sinonasal mass. After successful chemotherapy, the patient is now scheduled for radiotherapy and subsequently follow-up to assess the response.